Bahasa sebagai Oleh-Oleh: Pemerolehan Bahasa Kedua di Perantauan - Pulungan, Alpi Anwar (Prosiding Seminar Nasional Humaniora, 2025)
Merantau is the right way to acquire a second language and even a second culture. Often migrants only bring gifts in the form of a new language and culture when going home. This paper aims to describe how the process of acquiring a second language overseas and the various factors that influence it and how culture influences the acquisition of a second language. This research is a qualitative research with an ethnographic model of communication. Data were obtained by using in-depth interviews, observation, participant tests and video recordings. The results of this study indicate that the second language acquisition process is in line with the acculturation stages, namely 1) preproduction and 2) early production in line with the honeymoon stage, 3) early speech corresponds to the culture shock stage, 4) intermediate fluency in line with integration and 5) giftedness in line with with acceptance. In addition, several factors that influence the acquisition are 1) initial knowledge, 2) environment and habits, 3) long wandering, 4) motivation and 5) the influence of the first language. Abstrak Merantau merupakan upaya yang tepat untuk memperoleh bahasa kedua bahkan juga budaya kedua. Seringkali perantau hanya membawa oleh-oleh berupa bahasa dan budaya baru saat mudik ke kampung halaman. Tulisan ini bertujuan mendeskripsikan bagaimana proses pemerolehan bahasa kedua di perantauan dan berbagai faktor yang mempengaruhinya serta bagaimana pengaruh budaya terhadap pemerolehan bahasa kedua. Penelitian ini merupakan penelitian kualitatif dengan model etnografi komunikasi. Data diperoleh dengan metode wawancara mendalam, observasi, tes partisipan, dan rekaman video. Hasil penelitian ini menunjukkan bahwa proses pemerolehan bahasa kedua sejalan dengan tahapan akulturasi yakni 1) praproduksi dan 2) produksi awal sejalan dengan tahap bulan madu, 3) awal bicara sejalan dengan tahap kejutan budaya, 4) fasih menengah sejalan dengan integrasi dan 5) berbakat sejalan dengan penerimaan. Selain itu, faktor yang mempengaruhi pemerolehannya yakni 1) pengetahuan awal, 2) lingkungan dan kebiasaan, 3) lama merantau, 4) motivasi, dan 5) pengaruh bahasa pertama.